Most West Germans Support NATO, but Many Lack Confidence in the U.S. Defense Commitment. - United States Information Agency. Office of Research.; Adler, Kenneth P. (Tufts University. Tisch Library., 2019)
Findings from a USIA-sponsored survey conducted in the Federal Republic of Germany (and in six other NATO countries) between late May and early July.; Foreign Opinion Note N-9/11/84-C